Management of Postoperative Discitis Following Lumber Discectomy (Bangladesh Journal of Neurosurgery, 2023)
Background: There is no established protocol for the treatment of postoperative lumbar discitis. There are still so many controversies regarding the treatment of postoperative discitis.Materials and Methods: A total of 23 cases of postoperative discitis were treated from July 01, 2018 to June 30, 2021 for a period of 3 years. Initially all the patients were treated conservatively with complete bed rest, antibiotic therapy and analgesics. Most of the patients were improved clinically but who did not respond to conservative treatment for at least 4 weeks were treated surgically.Results Out of 23 patients, 11 (48%) patients showed significant clinical improvement after 4 weeks of starting treatment. 12 patients who failed to improve by conservative treatment were selected for surgical treatment. Among them in 5 (22%) patients only surgical debridement were done and in remaining 7 (30%) patients surgical debridement and posterior fixation were done. Most of the patients were improved by conservative treatment and among two groups of surgical treatment the fixation group showed early clinical improvement.Conclusions Early diagnosis and appropriate management is the key for effective treatment of postoperative discitis. Conservative management leads to an excellent result in majority of cases. Surgical intervention with or without posterior fusion is helpful when conservative treatment fails.Bang. J Neurosurgery 2022; 12(1): 6-11